Keyakinan terhadap Kitab Al Qur-An Terkait Penyembuhan - Farhan Lutfhi Azidan,; Zikri Raudhatul Ahsan, (Student Scientific Creativity Journal, 2024)
The Qur'an plays a major role in guiding humans to learn, gain knowledge, and direct all aspects of life both individually and socially in a positive direction. With the content of guidance, advice, and perfect laws, the Qur'an is the main source of reference for Muslims in living their daily lives and achieving success in this world and in the hereafter.The method that researchers use is descriptive qualitative research. Descriptive qualitative research is research conducted thoroughly on an object. The researcher becomes the main instrument in a qualitative study. Then, the results presented by the researcher are explained in the form of words obtained through valid data. Because qualitative research emphasizes meaning rather than generalization, and also the data cannot be resolved with statistical counts. The treatment process that occurs in one of the Tanjungpinang Kota communities affected by sticking disease is with the help of Koranic verses recited by the ustadz using mineral water media. The mineral water used is the condition that will be used in the treatment process. The water is then read the verses of the Qur'an by the ustadz and washed to several parts of the body of the person affected by sticking disease such as washing the head, hands, feet and finally the face. This paper describes the community's belief in the Qur'ān as a source of healing, which is deeply rooted in Islamic tradition and widely practiced in various Muslim communities, including in Tanjungpinang. The Qur'ān is not only seen as a holy book with high spiritual value but also as a source of alternative medicine that can cure physical, mental and spiritual illnesses.